Nitrogen fertilizer effects on the melon crop yield - Soares, José Monteiro; Brito, Luiza Teixeira de Lima; Costa, Nivaldo Duarte; Maciel, José Lins; Faria, Clementino Marcos Batista de (Pesquisa Agropecuaria Brasileira, 1999)
A study was carried at Petrolina-PE, Brazil, with the melon crop (Cucumis melo L.), cv. Valenciano Amarelo, in a Red-Yellow Latosol with the objective of evaluating the effect of nitrogen fertilizers sources and their combinations, applied through the conventional way and through water irrigation during the crop cycle. The experimental design was a split block with four replications and nine treatments: 1. control (without N); 2. urea; 3. ammonium sulphate, both applied conventionally; 4. urea applied up to 42 days after germination; 5. ammonium sulphate applied up to 42 days after germination; 6. urea applied up to 15 days and potassium nitrate from 16 to 42 days after germination; 7. urea applied up to 15 days and ammonium sulphate from 16 to 42 days; 8. urea applied up to 30 days and potassium nitrate from 31 to 42 days, and 9. urea applied up to 15 days, ammonium sulphate from 16 to 30 days and potassium nitrate from 31 to 42 days, at the level of 80 kg/ha of N. The fertilizers used during the crop cycle (treatments 4 to 9) were applied through irrigation water. It was found that urea applied through fertirrigation up to 42 days provided higher yield (31.14 ton/ha), not differing, however, from the other treatments, with the exception of the control and ammonium sulphate, which gave the lowest yields (25.06 and 24.65 ton/ha, respectively). It was found a variation in fruit mean weight from 1.63 to 1.84 kg/fruit. There was no significant difference in total soluble solid content (oBrix ) among the treatments.